Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.2 - Rational Exponents - Exercise Set - Page 426: 122



Work Step by Step

Let the missing term be $x$ The given expression becomes, $\frac{x}{y^{\frac{-3}{4}}}= y^{\frac{4}{4}}$ $x=y^{\frac{-3}{4}} \times y^{\frac{4}{4}}$ Using product rule for exponents, $a^{m} \times a^{n} = a^{m+n}$ $x=y^{\frac{-3}{4} + \frac{4}{4} } $ $x=y^{\frac{-3+4}{4} } $ $x=y^{\frac{1}{4} } $
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.